2011
DOI: 10.1074/jbc.m110.161414
|View full text |Cite
|
Sign up to set email alerts
|

No Reduction of Atherosclerosis in C-reactive Protein (CRP)-deficient Mice

Abstract: C-reactive protein (CRP), a phylogenetically highly conserved plasma protein, is the classical acute phase reactant in humans. Upon infection, inflammation, or tissue damage, its plasma level can rise within hours >1000-fold, providing an early, nonspecific disease indicator of prime clinical importance. In recent years, another aspect of CRP expression has attracted much scientific and public attention. Apart from transient, acute phase-associated spikes in plasma concentration, highly sensitive measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
58
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 38 publications
4
58
1
Order By: Relevance
“…(17). Consistent with previous reports (23,24), we found that neither plasma CRP nor SAP was elevated by diet-induced obesity in mice (Supplemental Figure 7, A and B). However, since SAP is the acute-phase reactant pentraxin in mice and CRP is not (25,26), and, as such, SAP abundance may change earlier during the genesis of obesity, we compared the development of obesity-induced insulin resistance in SAP +/+ with that of SAP -/-mice.…”
Section: Hfd-fed Fcγriibsupporting
confidence: 82%
“…(17). Consistent with previous reports (23,24), we found that neither plasma CRP nor SAP was elevated by diet-induced obesity in mice (Supplemental Figure 7, A and B). However, since SAP is the acute-phase reactant pentraxin in mice and CRP is not (25,26), and, as such, SAP abundance may change earlier during the genesis of obesity, we compared the development of obesity-induced insulin resistance in SAP +/+ with that of SAP -/-mice.…”
Section: Hfd-fed Fcγriibsupporting
confidence: 82%
“…Today, little is known about the in vivo effects of mCRP, partially due to lack of suitable animal models. In this context, Teupser et al could show that CRP-deficient mice developed atherosclerosis to the same degree as the control group (60). Neither the reduction of CRP serum concentration nor its complete absence resulted in a significant reduction of atherosclerotic lesions in the brachiocephalic arteries and aortic roots in two distinct mouse models of atherogenesis including a morphometric analysis of 240 animals.…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…LOX-1 is yet another PAMP-recognizing receptor with a key role in innate immunity (728), being activated by certain gram-positive and gram-negative bacteria, apoptotic bodies, senescent red blood cells, activated white blood cells (WBC) and platelets, advanced glycation end-products (AGEs), lysolecithin, and C-reactive protein (CRP) (561,1621). Note, however, that transgenic CRP overexpression studies and a recently reported CRP knockout have failed to demonstrate any proatherogenic effect for CRP (see TABLE 9) (1778), consistent with the lack of causal effects in human "Mendelian randomization" studies (474).…”
Section: Role Of the Oxidized Ldl Receptormentioning
confidence: 99%